THE EFFECT OF TASK BASED LANGUAGE TEACHING ON STUDENTS’ WRITING SKILL - Darojah, Ilma; Hidayat, Muhamad Taufik (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The objective of this study was to find out the significant effect of Task Based Language Teaching towards students’ writing ability. The research method used in this study was quantitative method with the pre-experimental design. The participants of this study were the tenth grade students in one of state vocational high schools in Garut at academic year 2019/2020. One class was chosen as sample of this study. One class was selected as an experimental class which consisted of 30 students. The data were collected through the result of students’ pre-test and post-test. The data were analyzed by using z-table formula. The result showed that zobserved = 13.012 and the significance level of 0,05; zcrirtical = z(0,5-0,05) = z0,450 = 1,65. Therefore, zobserved = 13.012 was greater than zcrirtical = 1,65, so that H0 was rejected and H was accepted. It could be concluded that there was a significant effect on students’ reading comprehension by using Read, Cover, Remember and Retell strategy